Response to Tumor Necrosis Factor Inhibitors in Rheumatoid Arthritis for Function and Pain is Affected by Rheumatoid Factor - Aberumand, Babak (Bentham Open, 2014)
OBJECTIVES : To investigate differences in response to tumor necrosis factor inhibitor treatment (TNFi) in seropositive (rheumatoid factor positive; RF+) versus seronegative (RF-) patients with established RA as measured by the Health Assessment Questionnaire Disability Index (HAQ-DI) and pain. METHODS : RA patients from an established RA cohort were studied according to rheumatoid factor (RF) status for change in HAQ-DI and pain (0-3 VAS) one year after starting treatment with a TNFi. RESULTS : There were 238 patients treated with TNFi who had follow-up data (178 RF+ and 60 RF-). Disease duration was longer in RF+ vs RF- (12+8 vs 8+8 years) but the proportion of females (82% vs 72%, P=0.7), baseline HAQ-DI (1.44+0.63 vs 1.41+0.63, P=0.8) and pain (1.92+0.67 vs 1.93+0.67, P=0.9) were not different. The mean duration of treatment of first TNFi was 2.8 vs 2.3 years, P=0.1 and 68% of RF+ vs 62% of RF- were still receiving first TNFi at last visit (P=0.5). For patients with data at baseline and one year, the one-year HAQ-DI change was significantly greater in 90 RF+ patients (-0.356) versus 38 RF- patients (-0.126; P=0.04). The mean pain improvement was also greater in 77 RF+ vs 32 RF- patients (-0.725 vs -0.332 respectively; P=0.03). Numbers are small, data are missing and comorbidities, DAS28 and anti-CCP were not collected. CONCLUSION : Despite limitations in the data, in established RA after failure of DMARDs, RF+ patients may be more responsive to TNFi therapy as measured by changes in HAQ-DI and pain. INNOVATION : There may be a better response to TNFi in RA if RF positive for function and pain.